Single cell RNA sequencing of human microglia uncovers a subset that is associated with Alzheimer's disease: Molecular and cell biology: Inflammatory and microglia‐mediated mechanisms in AD. (7th December 2020) - Olah, Marta; Menon, Vilas; Habib, Naomi; Taga, Mariko; Ma, Yiyi; Khairallah, Anthony; Yung, Christina J.; Coronas‐Samano, Guillermo; Vonsattel, Jean P; Teich, Andrew F.; Schneider, Julie A.; Bennett, David A.; et al.
Abstract: Background: The extent of microglial heterogeneity in the aging human brain remains a central, yet poorly explored question in light of the development of therapies targeting this cell type in age related neurodegenerative diseases, such as Alzheimer's disease. Methods: Using single cell RNA sequencing, we investigated the population structure of microglia purified from human cerebral cortex of aged donors with and without Alzheimer's disease. Results: We describe the population structure of microglia in the aged human brain and establish the divergent association of the different microglia subsets to age related neuropathologies and measures of cognitive decline. We confirm the presence of the identified microglial subpopulations histologically and explore their topological relationship to histopathological hallmarks of aging and AD in situ. Based on our data we prioritize one microglial cluster, cluster 7, which is enriched for genes involved in endosomal/vacuolar pathway. Interestingly we find that the signature gene set of cluster 7 is depleted in the cortical transcriptomic profile of individuals with AD. Histologically, these cluster 7 microglia are reduced in frequency in AD tissue, and we validate this observation in an independent set of single nucleus data. Conclusions: Thus, single cell transcriptomic profiling of live human microglia identifies a range of microglia subtypes in the aged human brain, and we prioritize one of these as being altered in AD.